PENGEMBANGAN EVALUASI PEMBELAJARAN BERBASIS WORDWALL PADA MATERI BAGIAN TUBUH TUMBUHAN DI SEKOLAH DASAR - Hanum Arifah Wiraserti, Dewi; Permana, Irvan; Destiana, Dita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Evaluation of wordwall-based learning on plant body parts material in elementary schools for class iv students at kartika xi-8 cibinong private elementary school. this research method uses the research and development (r&d) method with the addie (analysis, design, development, implementation, evaluation) development model. this research involved 28 students and in the process of validation and trial evaluation of the learning that had been developed. validation was carried out by three experts, namely media experts, linguists and material experts, with media expert validation results of 96%, linguist validation results of 100%, and material expert validation results of 96%, with an average result of 97.3% which is included in the "very eligible" criteria. the trial results showed an average score of 91.4% of the students. from these results, it can be concluded that the learning evaluation developed is very effective and practical for use in measuring students understanding of the plant body parts material.